40 Irradiation in molecular nanodroplets. (December 2018) - Salbaing, T.; Feketeová, L.; Abdoul-Carime, H.; Farizon, B.; Farizon, M.; Calvo, F.; Märk, T.D.
Abstract : Introduction: One of the specificities of ionizing radiations is that they interact with the electrons of the irradiated matter. In a molecular system the electrons are localized in molecules and the energy is initially deposited in the form of electronic excitation of one of the molecules. The description of the radiation of such initially deposited energy on the nanometer scale in the nearby molecules is challenging, in particular in the context of the therapies combining irradiation and radiosensitizers. Methods: The originality of the work consists of the study of "model" molecular nanosystems by both, the experiment and the theory. The nanodroplets are initially prepared with a given number of molecules. After a single ultrafast energy deposition located in one of the molecules, the nanodroplet is analyzed after a given relaxation time. The method combining mass spectrometry and imaging techniques allows the analysis of each nanodroplet and this is done for a large number of nanodroplets[1] . The results are compared with statistical molecular dynamics calculations[2] . Results: Thermalisation in nanodroplets following the sudden electronic excitation of one of the molecules[3] is observed with respect to the number of molecules (2–10 typically) in the nanodroplet and for several different types of nanodroplets: protonated water nanodroplets, water nanodroplets including an hydrophobic impurity, protonated methanol nanodroplets. The results show that the evaporation of a molecule takes place also before the full thermalisation of the nanodroplet through the ejection of a molecule with a speed clearly higher than that observed after full thermalisation. The measurements on the methanol nanodroplets evidence a competition between the evaporation of a molecule of methanol and a reaction between the molecules leading to the elimination of a water molecule. Conclusions: The quantitative comparison between the experimental results and the theoretical calculations for molecular nanosystems irradiated in the gas-phase paves the way to robust modelling of the irradiation mechanisms on the nanometer scale.